GAH-1 HÁM GAH-2 REAGENTLERI JÁRDEMINDE Fe(III), Hg(II) HÁM Pb(II) IONLARÍN SPEKTROFOTOMETRIYALÍQ ANÍQLAW - Askarova, Maral Raxmetovna (SCIENCE and SOCIETY, 2026)
The article investigates the optimal conditions for spectrophotometric determination of Fe(III), Hg(II), and Pb(II) ions using GAH-1 and GAH-2 reagents. The composition of the complexes was established by isomolar series and Asmus methods. Dissociation constants, molar absorptivity coefficients, equilibrium constants, and stability constants were determined. The developed method was successfully applied to synthetic mixtures and natural water samples.